THE INFLUENCE OF GROWTH OPPORTUNITIES, DEBT POLICY, AND SOLVENCY ON COMPANY VALUE - Nurainun Bangun; Khairina Natsir; Ngadiman Ngadiman (International Journal of Application on Economics and Business, 2024)
This study aims to prove the influence of growth opportunity, debt policy, and solvency on company value in basic industrial and chemical companies listed on the Indonesia Stock Exchange from 2019 to 2021. A total of 27 selected samples with a total of 81 observations over three years were used in the research. This. Research data is secondary data extracted from company annual financial reports that have been audited and published. Panel data was processed with the help of Eviews version 12 software. Data analysis uses multiple linear regression. The testing stages include the classic assumption test consisting of multicollinearity and heteroscedasticity tests, then selecting the most appropriate regression model using the Chow test, Hausman test and Lagrange Multiplier test. Research hypothesis testing was carried out by a t-test and coefficient of determination test. The results of the analysis show that growth opportunity partially has a negative effect on company value, debt policy has an insignificant positive effect on company value, and solvency has a significant positive effect on the value of basic industrial and chemical companies listed on the Indonesia Stock Exchange in the 2019-2021 period.